Endoscopic ultra-sound (EUS) guided management of symptomatic pelvic collections: puncture-aspiration or drainage? Results from mono-centric retrospective experience with therapeutic algorithm. (2nd January 2022) - Guingand, Marine; Gasmi, Mohamed; Serrero, Mélanie; Barthet, Marc; Gonzalez, Jean-Michel
Abstract: Background: Pelvic collections may occur after surgery or in medical diseases. EUS transmural (TM) treatment has been shown as highly effective and safe, becoming an alternative to surgery or radiology. We aimed to assess the results of EUS management of pelvic collections. Methods: Retrospective, single-center observational study conducted between 2004 and 2018. Patients with symptomatic collections treated by EUS-TM approach were enrolled. The procedures were performed with a therapeutic EUS-scope, following two possible options: puncture-aspiration-injection of antibiotics PAIA (group 1) or EUS-drainage by plastic double pigtail stents (DPS) with an ano-cavitary drain (ACD) or lumen-apposing metal Stent (LAMS) (group 2). The main objective was to assess the clinical effectiveness based on symptoms and collection resolution. Results: Seventy-three patients were included. Mean age was 42.5 years [12–87]. 30 patients in group 1 (41%) underwent PAIA and 43 in group 2 (59%) underwent DPS ± ACD in 41 patients (95%) and LAMS in 2. The collection was postoperative in 58%. The mean size was 48.9 mm [8–120], 33 +/- 17 mm in group 1, compared to 67 ± 21 mm in group 2 ( p  < .0001). All the procedures were technically successful. Overall clinical success was 96% (93% in group 1 (28/30), 98% (42/43) in group 2). Failures occurred in 2 post sigmoiditis abscesses and 1 ileo-colic Crohn's disease. No adverse event was reported. During the median follow-up of 7.5 years [4.4–8.9], no patient had recurrence. Conclusions: EUS-TM with either PAIA or drainage depending on the collection size is confirmed to be highly effective and safe.